Real convergence and the determinants of growth in EU candidate and potential candidate countries - a panel data approach - Magdalena Morgese Borys; Éva Katalin Polgár; Andrei Zlate (European Central Bank (ECB), 2008)
The EU candidate and potential candidate countries have made considerable progress in economic transition and integration into the world economy within less than two decades. Nevertheless, gaps in terms of income per capita relative to the euro area remain large. This suggests that the challenges of real convergence will remain relevant for the region even in the medium and long term. This paper therefore focuses on real convergence and its determinants in the candidate and potential candidate countries. The analysis reveals that total factor productivity growth has been the main driver of convergence, followed by capital deepening, whereas labour has contributed only marginally to economic growth. There is evidence of conditional convergence in the transition countries of central, eastern and south-eastern Europe. More specifi cally, controlling for the quality of institutions, the extent of market reforms and macroeconomic policies, there is a significant and negative link between the initial level of GDP and subsequent growth. Labour productivity has improved in most countries, while employment and participation rates have been falling. Structural changes have resulted in, at least temporarily, increasing labour market mismatches. Investment rates have been rising rapidly in recent years, and foreign direct investment has been found to have a positive impact on total investment. Investment in human capital is still at a relatively low level compared with the euro area average. Thus, in order to sustain the positive developments observed in the past, further improvements are needed in terms of labour productivity and utilisation, as well as in terms of physical and human capital accumulation.
Keywords: F15; F43; O16; O43; O47; O52; 330; Real convergence; conditional convergence; determinants of growth; total factor productivity; labour markets; capital accumulation; EU candidate and potential candidate countries.; EU-Mitgliedschaft; Wirtschaftliche Konvergenz; Wirtschaftswachstum; Produktivität; Arbeitsmarkt; Investition; Kroatien; Mazedonien; Türkei; Albanien; Bosnien-Herzegowina; Serbien-Montenegro